Recruitment strategies for Turkish immigrants in dementia care research: a scoping review - Esma Inam; Seda Güney; Martina Roes (BMC Geriatrics)
Abstract Background Among the ethnic minority groups in Germany, Turkish immigrants represent the largest community. At the same time, this target group is underrepresented in dementia care research, and there are unique challenges regarding the recruitment of this group for studies. Increasing the involvement of Turkish immigrants in dementia care research is essential for reducing dementia-related inequalities. The aim of this scoping review is to describe strategies for recruiting Turkish immigrants living with dementia and their caregiving relatives for dementia care research and to identify related recruitment challenges. Methods We conducted a scoping review including articles from peer-reviewed journals applying the methodological framework of Arksey and O'Malley and the PCC framework (P = Population, C = Concept, C = Context). We searched the MEDLINE, PsycINFO, CINAHL, and Scopus databases as well as the literature written in the German language in local university databases. There were no restrictions on publication dates or study types. Additionally, the references of the identified articles were manually searched, and relevant articles were added. The content analysis was used to synthesize the findings. Results In total, 651 articles were screened, 15 of which were included in the review. Nine of the 15 articles were focused on the involvement of caregiving relatives, and six of the included articles were focused on people with dementia. The choice of recruitment strategies depended on the specific target group. Five main categories were identified based on the characteristics of the recruitment strategies implemented: Access to health environment, inclusive practices and cultural considerations, face-to-face interactions, technology-mediated access and engagement events. People with dementia were recruited predominantly through senior centres, hospitals, or home care providers; referrals from physicians; and databases/registries. The involvement of bilingual staff was a crucial strategy for achieving greater participation. Caregiving relatives were recruited mainly through dementia-related community organizations, settings, and social networks and through the involvement of bilingual staff. While facilitators play an essential role in engaging caregiving relatives, language and cultural barriers remain the most important barriers. Conclusions The persistent presence of language and cultural barriers requires a culturally sensitive recruitment approach to increase the involvement of Turkish immigrants living with dementia and their caregiving relatives in dementia care research.